2011
DOI: 10.1002/jnr.22733
|View full text |Cite
|
Sign up to set email alerts
|

Proline substitutions and threonine pseudophosphorylation of the SH3 ligand of 18.5‐kDa myelin basic protein decrease its affinity for the Fyn‐SH3 domain and alter process development and protein localization in oligodendrocytes

Abstract: The developmentally regulated myelin basic proteins (MBPs), which arise from the golli (gene of oligodendrocyte lineage) complex, are highly positively charged, intrinsically disordered, multifunctional proteins having several alternatively spliced isoforms and posttranslational modifications, and they play key roles in myelin compaction. The classic 18.5-kDa MBP isoform has a proline-rich region comprising amino acids 92-99 (murine sequence -T(92)PRTPPPS(99)-) that contains a minimal SH3 ligand domain. We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(102 citation statements)
references
References 96 publications
(148 reference statements)
8
94
0
Order By: Relevance
“…These minor MBP isoforms have been observed in the nucleus of primary OLG cultures and OLGs in the mouse brain [25][26][27] and are also enriched in the radial component of compact myelin [28,29]. We have found that full-length 21.5-kDa MBP was still localized primarily to the nucleus despite the presence of the 3′UTR [20][21][22]. The minor isoforms have been speculated to play key developmental roles that may regulate myelinogenesis [25,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…These minor MBP isoforms have been observed in the nucleus of primary OLG cultures and OLGs in the mouse brain [25][26][27] and are also enriched in the radial component of compact myelin [28,29]. We have found that full-length 21.5-kDa MBP was still localized primarily to the nucleus despite the presence of the 3′UTR [20][21][22]. The minor isoforms have been speculated to play key developmental roles that may regulate myelinogenesis [25,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 77%
“…1A) significantly decrease calcium influx, via voltage operated calcium channels into primary OLGs and immortalized N19-OLG cells, in contrast to Golli isoforms [20], and that stimulation with a phorbol ester (phorbol-12-myristate-13-acetate), and with IGF-1 (insulin-like growth factor-1), spatially redistributes MBP to distinct membrane 'ruffled' regions at the cell cortex, where it associates with β-and γ-actin, cortactin, and α-tubulin [21]. Additionally, we have shown that the expression of classic 18.5-kDa MBP with the constitutively-active form of Fyn-kinase causes extensive membrane elaboration, and branching complexity at the forefront of extending N19-OLG membrane processes, a phenomenon that is abolished by substituting either proline residue within its PXXP SH3-ligand consensus motif [22]. These results demonstrate that 18.5-kDa MBP participates in and/or mediates cytoskeletal protein-protein interactions at the cytoplasmic leaflet during membrane remodeling in developing OLGs, and that several of these interactions may be facilitated by SH3-ligand domain binding of MBP with other proteins.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations